Communication-efficient bitonic sort on a distributed memory parallel computer - Yong Cheol Kim; Minsoo Jeon; Dongseung Kim; Sohn, A. (Proceedings. Eighth International Conference on Parallel and Distributed Systems. ICPADS 2001, 2001)
Sort can be speeded up on parallel computers by dividing and computing data individually in parallel. Bitonic sorting can be parallelized, however, a great portion of execution time is consumed due to O(log/sup 2/P) time of data exchange of N/P keys where P, N are the number of processors and keys, respectively. This paper presents an efficient way of data communication in bitonic sort to minimize the interprocessor communication and comparison time. Before actual data movement, each pair processor exchanges the minimum and maximum in its list of keys to determine which keys are to be sent to its partner. Very often no keys need to exchange, or only a fraction of them are exchanged. At least 20% or greater of execution time could be reduced on the T3E computer in our experiments. We believe the scheme is a good way to shorten the communication time in similar applications.